1989
DOI: 10.1161/01.hyp.13.6.766
|View full text |Cite
|
Sign up to set email alerts
|

Long-term improvement in renal function after short-term strict blood pressure control in hypertensive nephrosclerosis.

Abstract: Seventy-nine hypertensive nephrosclerosis patients i entered a prospective randomized singleblind study to 1) establish the pattern of decay of renal function in this population and the variability therein and 2) to determine if strict diastolic blood pressure (DBP) control (<80 mm Hg) is more effective than conventional levels (90-95 mm Hg) in conserving renal function. Because of unexpected significant improvement in renal function in patients from both groups, which changed the perspectives on the course of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
3

Year Published

1990
1990
2006
2006

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(27 citation statements)
references
References 31 publications
0
24
0
3
Order By: Relevance
“…Illicit drug use, however, was not found to be a risk factor for severe hypertension in a black and Hispanic population (93). Despite the plausible putative effects of cocaine on the kidney and vasculature, medical noncompliance and socioeconomic factors may contribute to the increased risk for renal deterioration in hypertensive black individuals (94,95). Diagnoses of hypertension-related ESRD often are made on clinical grounds alone, so the validity of reported causes of ESRD may be uncertain without verification by renal biopsy (92).…”
Section: Pathophysiologic Basis For Renal Diseasementioning
confidence: 99%
“…Illicit drug use, however, was not found to be a risk factor for severe hypertension in a black and Hispanic population (93). Despite the plausible putative effects of cocaine on the kidney and vasculature, medical noncompliance and socioeconomic factors may contribute to the increased risk for renal deterioration in hypertensive black individuals (94,95). Diagnoses of hypertension-related ESRD often are made on clinical grounds alone, so the validity of reported causes of ESRD may be uncertain without verification by renal biopsy (92).…”
Section: Pathophysiologic Basis For Renal Diseasementioning
confidence: 99%
“…In contrast, in a study over several years but with patient groups partially separated into two levels of target blood pressure, GFR was apparently maintained by therapy that included minoxidil. 85 Several retrospective studies have shown no evidence of renal protection by apparently effective antihypertensive treatment, especially in African-Americans. 86 " 89 In an important analysis of the Multiple Risk Factor Intervention Trial (MRFIT), admittedly using reciprocal serum creatinine measurements but over 8 years and with well-documented good control of blood pressure (to 132/87 mm Hg in the "usual care" group and 121/82 mm Hg in the "special intervention" group), Walker and coworkers 89 demonstrated protection of renal function in white but not in black subjects.…”
Section: Lack Of Prevention Of End-stage Renal Diseasementioning
confidence: 99%
“…However, the clinical literature had already suggested the importance of diabetes management [11], blood pressure control [12][13][14][15], angiotensin-converting enzyme inhibition (ACEI) [16], anemia management [17,18], management of calcium metabolism [19][20][21], and timely referral to nephrologist [4,5,22].…”
Section: Introductionmentioning
confidence: 99%